Peptide‐modified stainless steel with resistance capacity of Staphylococcus aureus biofilm formation. (3rd September 2018) - Cao, Pan; He, Xiaoyan; Xiao, Jinfei; Yuan, Chengqing; Bai, Xiuqin
Abstract : Attachment of marine fouling organisms causes biofouling. The adhesion of destructive organisms can be reduced through surface modification with antibiofilm chemicals. In this study, a direct surface modification between peptide solution with different concentrations and stainless steel was performed, and the reaction mechanism was explained by simulation of the modification process. Results of surface water contact angle and surface hardness indicated the optimal modification concentration of peptide solution was 10 μg/mL. Under the optimal concentration, peptide‐modified stainless steel was prepared through the reaction between peptide and 304 stainless steel. Results of scanning electron microscopy equipped with energy dispersive spectrometry, Fourier transform infrared spectroscopy, and X‐ray photoelectron spectroscopy demonstrated that the peptide was successfully bound on stainless steel surface. Antimicrobial activity of samples surface was tested against Staphylococcus aureus . The results illustrated that the peptide treated sample surface possesses significant antimicrobial property. The findings presented valuable information on marine antifouling researches.